Subtype-specific regulation of P2X3 and P2X2/3 receptors by phosphoinositides in peripheral nociceptors - Logothetis Diomedes; Ase Ariel R; Chabot-Dor; Zhao Qi; Bernier Louis-Philippe; Mo Gary; Cao Chang-Qing; Séguéla Philippe (SAGE Publishing, 2009)
Abstract Background P2X3 and P2X2/3 purinergic receptor-channels, expressed in primary sensory neurons that mediate nociception, have been implicated in neuropathic and inflammatory pain responses. The phospholipids phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidylinositol 3,4,5-trisphosphate (PIP3) are involved in functional modulation of several types of ion channels. We report here evidence that these phospholipids are able to modulate the function of homomeric P2X3 and heteromeric P2X2/3 purinoceptors expressed in dorsal root ganglion (DRG) nociceptors and in heterologous expression systems. Results In dissociated rat DRG neurons, incubation with the PI3K/PI4K inhibitor wortmannin at 35 μM induced a dramatic decrease in the amplitude of ATP- or α,β-meATP-evoked P2X3 currents, while incubation with 100 nM wortmannin (selective PI3K inhibition) produced no significant effect. Intracellular application of PIP2 was able to fully reverse the inhibition of P2X3 currents induced by wortmannin. In Xenopus oocytes and in HEK293 cells expressing recombinant P2X3, 35 μM wortmannin incubation induced a significant decrease in the rate of receptor recovery. Native and recombinant P2X2/3 receptor-mediated currents were inhibited by incubation with wortmannin both at 35 μM and 100 nM. The decrease of P2X2/3 current amplitude induced by wortmannin could be partially reversed by application of PIP2 or PIP3, indicating a sensitivity to both phosphoinositides in DRG neurons and Xenopus oocytes. Using a lipid binding assay, we demonstrate that the C-terminus of the P2X2 subunit binds directly to PIP2, PIP3 and other phosphoinositides. In contrast, no direct binding was detected between the C-terminus of P2X3 subunit and phosphoinositides. Conclusion Our findings indicate a functional regulation of homomeric P2X3 and heteromeric P2X2/3 ATP receptors by phosphoinositides in the plasma membrane of DRG nociceptors, based on subtype-specific mechanisms of direct and indirect lipid sensing.